Metode Pendidikan Akhlak Ibn Miskawaih dan Relevansinya terhadap Pendidikan Karakter di Era Modern - Taubatan Nasuha; Dian Namora (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2026)
Method of moral education is crucial for shaping and nurturing one’s perspective on physical, intellectual, mental, and moral development. Today’s modern era brings rapid technological and informational advancements, yet it has also given rise to serious concerns in the realm of moral education, as well as a crisis of identity and character among the younger generation. Exposure to social media, a culture of hedonism, and the tide of secularism have eroded noble values such as honesty, trustworthiness, a sense of shame regarding immoral acts, and respect for teachers. Many students are academically intelligent but morally and spiritually fragile. This qualitative study, conducted as library research, examines the ideas of Ibn Miskawaih. The analysis is based on documentation from primary sources specifically the book Tahdzib Al-Akhlaq and secondary sources, such as relevant print and digital literature related to the discussion. The findings of this study are as follows: According to Ibn Miskawaih, ethics is the soul’s impulse to act without first consulting reason. According to Ibn Miskawaih, the goal of ethical education is to cultivate an inner disposition that can spontaneously inspire all good deeds, thereby achieving perfection and attaining true and complete happiness. Ibn Miskawaih identifies three main sources for moral education: First, the elements necessary for the functioning of the human body; second, the needs of the soul; and third, the needs for interpersonal relationships. Natural methods, counsel, habituation, riyadhah, and punishment constitute Ibn Miskawaih’s approach to moral education. Character education places greater emphasis on social behavior and the cultivation of attitudes. According to Law No. 20 of 2003 on the National Education System, Ibn Miskawaih’s concept of moral education remains relevant to character education today.